Intimate partner violence, intergenerational transmission, and subjective well-being in young university students in Northeastern Mexico - Carrizales Berlanga, Daniella; Molina Coloma, Verónica Alexandra; Reyes-Sosa, Hiram; Zamudio Elizalde, Pedro Damián; Garza Sánchez, Rosa Isabel (Pensando Psicología, 2024)
Objective. To analyze the relationship between intimate partner violence, intergenerational transmission, and subjective well-being, as well as to identify gender differences in young university students in northeastern Mexico. Method. A non-experimental, transitional design with descriptive, correlational and comparative scope was used. The CTS 2 Conflict Tactics Scale, the Intergenerational Transmission Questionnaire and the PERMA Profile Survey were used. Results. The psychological aggression dimension obtained a high score, as well as the violent pattern dimension. Regarding subjective well-being, the highest score was the interpersonal relationships dimension. A significant relationship was found between violence in intimate partner relationships, intergenerational transmission and subjective well-being, highlighting that psychological and physical aggression have a direct relationship with violent patterns. Some dimensions (commitment and interpersonal relationships) of subjective well-being decrease to the extent that violent patterns occur in the family. No significant differences were found between sexes in the dimensions of violence exercised, however, a statistically significant difference was observed in the violence suffered, where men receive greater psychological aggression than women. Conclusion. It is concluded that psychological violence is the one that occurs most in the relationships of university students, the addictive and violent pattern influence their behavior in the relationship. On the other hand, the subjective well-being of the university students was good.